From self-regulated learning to computer-delivered integrated speaking testing: Does monitoring always monitor? - Zhang, Weiwei; Wilson, Aaron (Frontiers in Psychology, 2023)
Despite the salience of monitoring in self-regulated learning (SRL) and L2 speech production in non-testing conditions, little is known about the metacognitive construct in testing contexts and its effects on learner performance. Learning and testing have widely recognised reciprocal in that the fundamental goal of language learning in any forms including SRL for many learners is to pass a certain test for either an academic purpose or for a vocational objective, and language testing exerts increasing backwash effects on language learning. Because of these reciprocal effects, a research effort in monitoring working in speaking tests, in particular computer-delivered integrated speaking tests, a testing format that has been advocated as an internal part of L2 classroom instruction due to its authenticity (Thomas, 2019) and its representativeness of future direction of L2 testing, is warranted. This study, therefore, serves as such an effort by investigating the use of monitoring by 95 Chinese English as foreign language (EFL) learners on a self-reported questionnaire after they performed three computer-delivered integrated speaking test tasks. Descriptive analysis followed by HLM testing reveals that monitoring was used in a high-frequency manner, but it exerted no substantial effects on learner performance. Primarily, the results are expected to provide pedagogical implications for SRL: While fostering self-regulating learners especially self-monitoring L2 speakers, it is necessary for L2 teachers to purposefully reduplicate testing conditions in their classroom instructions for helping the self-regulating learners be equally self-regulating test-takers assisted by monitoring to pass the tests. Moreover, the results are hoped to offer some insights into L2 testing through the perspective of self-monitoring, one proposed component of strategic competence, a construct that has been extensively acknowledged to reflect the essence of L2 testing.